2000
DOI: 10.1046/j.1439-0442.2000.00290.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Experiences of Treating Septic Arthritis in the Equine by Repeated Joint Lavage: a Series of 39 Cases

Abstract: The condition of septic arthritis was treated in 12 foals with 21 affected joints (Group I) and in 27 adult horses. The adult horses were divided into three groups, based on aetiology of the condition: haematogenous (Group II, n = 6), iatrogenic (Group III, n = 6), and perforating trauma (Group IV, n = 15). The treatment consisted of an initial systemic antibiotic that anticipated the microbial agents that were considered most likely per group, repeated through-and-through joint lavages every other day and non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
103
1
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(114 citation statements)
references
References 15 publications
4
103
1
4
Order By: Relevance
“…The tarsocrural joint was most commonly affected in cases of septic arthritis followed by the fetlock joint, which corresponds with the literature. 24,35,51 When referring to synovial sheaths, the digital flexor sheath was mostly affected both in septic cases and in lacerations, as reported. 15,31,32,40 Regional limb perfusion with antimicrobials was used for a variety of conditions in the horses in group 3.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The tarsocrural joint was most commonly affected in cases of septic arthritis followed by the fetlock joint, which corresponds with the literature. 24,35,51 When referring to synovial sheaths, the digital flexor sheath was mostly affected both in septic cases and in lacerations, as reported. 15,31,32,40 Regional limb perfusion with antimicrobials was used for a variety of conditions in the horses in group 3.…”
Section: Discussionmentioning
confidence: 87%
“…It was our purpose to be as specific as possible when defining sepsis in a synovial structure and to evaluate septic synovitis and nonseptic contaminated intrasynovial lacerations separately. Previous studies 15,24,[33][34][35][36][37][38][39] evaluating septic synovitis in horses have found survival rates of 62% to 92% in adults and 42% to 85% in foals. In our study, 72% of horses with septic synovitis were discharged from the hospital, and 53.43% of the horses with follow-up information available were alive at long-term follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Such reactions are much less common with the use of local anaesthetics than other medications (Ross et al 2003). However, it is one of the most difficult conditions to differentiate from a synovial infection (Kuemmerle et al 2006), which itself is also a possible sequela of a lameness examination when an intrasynovial anaesthesia has been performed (Schneider et al 1992a, Meijer et al 2000, Ross et al 2003, Bergman 2010). The clinical signs are similar (severe lameness, joint distension and an acute inflammation inside the joint) and there are no easy means of differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…The aetiology of the infection has a significant effect on the type of bacteria identified by culture (Schneider et al 1992a). Horses that develop an infection secondary to a penetrating wound frequently provide cultures of more than one organism (Schneider et al 1992a, Meijer et al 2000, Taylor et al 2010. In this case, only one organism, a Methicillin-ResistentStaphylococcus-Aureus (MRSA) was cultured from the DFTS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation